The bidirectional relationships between social isolation and cognitive function among older adults in China: separating between-person effects from within-person effects - Xinlong Xie; Fanfan Wu; Zhiruo Zhuang; Aijun Xu (Scientific Reports)
Abstract This study investigates the bidirectional relationship between social isolation and cognitive function among older adults in China, utilizing data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). The baseline survey, which commenced in 2008, tracked 1,662 participants over four waves of data collection spanning a decade. We employed Cross-Lagged Panel Models (CLPM) and Random Intercept Cross-Lagged Panel Models (RI-CLPM) to analyze these relationships at both the between-person and within-person levels. CLPM results indicated significant cross-lagged effects between social isolation (β = − 0.119, p < 0.001; β = − 0.162, p < 0.001) and cognitive function (β = − 0.073, p < 0.001; β = − 0.091, p < 0.001) at the between-person level over the last three waves. Specifically, higher prior levels of social isolation were associated with a significant decline in subsequent cognitive function, and vice versa. Furthermore, RI-CLPM results showed that, after controlling for random intercepts and covariates, only social isolation had a significant negative impact on cognitive function across all waves (β = − 0.051, p < 0.05; β = − 0.047, p < 0.05; β = − 0.028, p < 0.05). Overall, this study demonstrates that, when considering both between-person and within-person effects, social isolation exerts a stronger lag effect on cognitive function among older adults in China. This suggests that, over a specific timeframe, reducing social isolation is crucial for promoting healthy aging in this population.